CONDITIONS FOR OVERCOMING COMMUNICATION-LANGUAGE BARRIERS IN THE SYSTEM OF NON-LINGUISTIC HIGHER EDUCATION - Polyakova, Lidiya Olegovna (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2016)
Purpose. The article substantiates the complex of organizational and pedagogical conditions for the solution of communicative and language barriers in the higher education system in modern Russia. Methodology. The basis of the research is the hermeneutic, formalized and comparative methods. Results. Results of our scientific work are such conditions should be implemented based on the principle of «vertical integration», covering the social levels of the customer of higher education (economic sector), national systems of higher education, the University, the faculty, the chair. Practical implications. Presents a set of tools that is effective in solving problems of communication-language barriers of future specialists of non-linguistic profile.